Pengaruh Waktu Respon Pada Sistem Keamanan Rumah Berbasis IOT dengan ESP32-Cam dan PIR Menggunakan SmartPhone Android - Gunawan T Hadiyanto; Heqal Satriafwi Gurran; Bambang Apriyanto; Ria Saptarika (STMIK Budi Darma, 2022)
Home security is priority for every home owner, the rise of crime rate in the housing area when they leave their house makes an innovation for security system in the housing area. Nowadays, humans want to get accurate and quick information and humans can't be separated from the smartphone. The implementation of smart home security system can be implemented with an Internet of Things system which can take pictures and provide real-time information to home owners via smartphones if an intruder is detected. With a PIR sensor (Passive Infrared) as a motion detector and a buzzer that will turn on when motion is detected, and an ESP32 CAM as a camera that will take pictures to visualized the incident directly. Motion security alarm is an application created to display all historical data that is detected by motion. The result of testing the security system get a 90% success percentage by sending sensor data and taking pictures automatically.